Life on the periphery is tough: Vegetation in Northwest Iceland and its responses to early-Holocene warmth and later climate fluctuations. (September 2015) - Eddudóttir, Sigrún D; Erlendsson, Egill; Gísladóttir, Guðrún
Long- and short-term climate variations in the North Atlantic have been of sufficient magnitude to leave a discernible mark on the history of vegetation and landscape stability in Iceland during the Holocene. A reconstruction of early- and mid-Holocene vegetation around Lake Kagaðarhóll, Northwest Iceland, examines how climate fluctuations have affected the terrestrial ecosystem. A thorough reconstruction has been made using pollen and plant macrofossil analyses combined with proxies for organic and inorganic matter. The record shows the development from a period of pioneer vegetation towards a woodland ecosystem. The deposition of the Saksunarvatn tephra at c . 10, 300 cal. yr BP caused a 100-year period of instability, followed by a gradual trend of stabilization over several centuries while material left behind by retreating glaciers and tephra was being contained by expanding and developing vegetation. Early-Holocene warmth is indicated by high pollen production of Juniperus communis around the lake by c . 10, 100 cal. yr BP and birch woodland being established around the lake by c . 9200 cal. yr BP, much earlier than previously believed for this locale. Cooling climate between c . 8700 and 8200 cal. yr BP halted woodland development, with reduced plant reproduction likely caused by cold spring and summer temperatures. Woodlands became re-established from c . 7900 cal. yr BP before entering a decline from c . 6000 cal. yr BP, with harsher environmental conditions apparent after c . 4200 cal. yr BP. The Kagaðarhóll record compares favourably with other palaeoclimatic data from the North Atlantic, demonstrating the potential of pollen and macrofossil data for reconstructions of environmental change in Iceland and as an indicator of climate variability in the North Atlantic during the Holocene.